Effect of Four Medicinal Plants on Amyloid-β Induced Neurotoxicity in SH-SY5Y Cells - Adewusi, Emanuel A (African Networks on Ethnomedicines, 2013)
Amyloid-beta peptide (Aβ) is implicated in the pathogenesis of Alzheimer's disease (AD), a neurodegenerative disorder. This study was designed to determine the effect of four medicinal plants used to treat neurodegenerative diseases on Aβ-induced cell death. Cytotoxicity of the ethanol extracts of the plants was determined against SH-SY5Y (human neuroblastoma) cells which were untreated, as well as toxically induced with Aβ, using the MTT and neutral red uptake assays. Cell viability was reduced to 16% when exposed to 20 µM Aβ(25–35) for 72 h. The methanol extract of the roots of Ziziphus mucronata Willd., Lannea schweinfurthii (Engl.) Engl. and Terminalia sericea Burch. ex DC., were the least toxic to the SH-SY5Ycells at the highest concentration tested (100 µg/ml). All four plants tested were observed to reduce the effects of Aβ-induced neuronal cell death, indicating that they may contain compounds which may be relevant in the prevention of AD progression.